Estudo ecotoxicológico de corante têxtil e remediação por Fenton e Fenton-like - Fernandes, Neemias Cintra (2018)
Azo dyes represent the most important class of textile dyes, being widely used in the pharmaceutical and food industry. These molecules are present in domestic and industrial wastewater, and are resistant to conventional effluent treatment eventually producing more toxic products than the original dyes. Advanced oxidative processes (AOPs) have been implemented in order to decompose or mineralize substances that are difficult to treat, reducing their toxicity and the inherent risks of releasing pollutants into the environment. Objective: To study the ecotoxicity and optimize the operational conditions in the decomposition of textile azo dye DR343 using Fenton and Fenton-like reactions. Method: Oxidative processes were studied using the factorial design Box-Behnken Design (BBD), and the optimization of the reaction conditions was performed by applying the desirability function. The pH of the medium, the reaction time, the concentrations of iron [Fe 2+ ] (Fenton) and [Fe 3+ ] (Fenton-like) as well as the oxidizing agent [H 2 O 2 ] were used as independent variables in the planning. The responses studied were the removal of DR343, the concentration of residual hydrogen peroxide [H 2 O 2residual ] and the mortality of Artemia salina. The toxicity of the untreated dye was evaluated in different organisms (lettuce seeds, Artemia salina and zebrafish embryos). Samples treated under optimal conditions were submitted to the same protocols. Results: The dye removal was in the range of 5.8% to 100%, being affected only by the concentration of catalyst [Fe 2+ /Fe 3+ ] in both processes. On the other hand, the process time had a significant effect on the mortality of A. salina in samples submitted to the Fenton process, which suggests formation of toxic oxidation byproducts at the beginning of the process, followed by the mineralization of the samples. Optimum conditions for the Fenton reaction included [Fe 2+ ] of 0.33 mmol.L -1 and [H 2 O 2 ] of 4.50 mmol.L -1 . Under these conditions, 100% of the dye decomposition was observed in 16.1 minutes. On the other hand, the optimal conditions of the Fenton-like process included [Fe 3 + ] of 0.25 mmol.L -1 and [H 2 O 2 ] of 0.54 mmol.L -1 . Under these conditions total dye decomposition was observed in only 9.2 minutes. No [H 2 O 2residual ] was detected in both optimized processes. No significant phytotoxic effects were observed on the untreated dye dispersions, nor after treatment in both procedures. In the case of the A. salina assays, differences between the two processes were observed. Samples treated by Fenton-like did not show significant toxicity, whereas the Fenton process induced significant mortality for this organism. Samples treated under optimal conditions, from both methods, did not induce lethal or sublethal effects on zebrafish embryos. Total organic carbon reduction of 52.0% and 34.8% was observed for Fenton and Fenton-like, respectively. Conclusion: Both the studied processes can be successfully used to decompose the DR343 dye in water, however, the Fenton reaction, despite obtaining better mineralization rates, produced more toxic by-products when compared to the Fenton-like process. The untreated dye did not show phytotoxicity, nor did it generate significant effects on zebrafish embryos.